The design and development of an Islamic calligraphy module for primary school children / Zuhalizan Khodir - Khodir, Zuhalizan (2013)
Calligraphy is the most important art form of Islamic culture because it is the most prevalent, the most significant, the most widely appreciated and the most recovered by Muslim. Islamic calligraphy considered as a unique art which spreading thousand spiritual messages but eroded gradually by the Muslim’s generation. Even though it has not been included directly in the Integrated Curriculum in Primary School (KBSR) or Curriculum Primary School (KSSR) arts syllabus, but it was adopted in Islamic Education Year 4, 5, and 6. Since the Ministry of Education (MOE) crucially emphasized on cross-curricular elements in creating a meaningful teaching and learning lessons, hereby arts could be served as the best tool to implement it. Hence, this study primarily highlights to investigate pupils’ interest and practices towards Islamic calligraphy and Jawi, respectively in Tangkak, Johor. The co relational research was conducted by using research instrument comprising skills and interest questionnaires in both fields. Based on questionnaires circulated amongst 150 respondents from Year 6 by using 5 points Likert scale, the data revealed that relationship between interest and practices always coexist together; similarly as resulted as studies conducted in other countries. Thus, a module developed for the primary school students to polish their skills in writing basic Nasakh calligraphy. Implications and ways of improving the current practices will be discussed further in order to ensure the extinction of this art would not occur for the future next generation.